Robust recognition of tactile gestures for intuitive robot programming and control - Kubus, Daniel; Muxfeldt, Arne; Kissener, Konrad; Haus, Jan; Steil, Jochen (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2017)
Tactile surface sensors (TSSs) are often utilized for contact management in human robot interaction scenarios. To provide added value in these applications, online robot programming approaches may exploit TSSs as gesture input devices. To this end, we introduce an invariant, compact gesture representation which facilitates robust and efficient online gesture recognition even for very small training data sets. The proposed two-stage recognition approach permits reliable gesture classification as well as convenient parameter extraction in the presence of typical disturbances affecting TSSs attached to manipulator links. Our experimental results demonstrate the remarkable recognition performance of the proposed approach using a set of 16 gestures and data of up to 31 subjects.